2000
DOI: 10.1116/1.582445
|View full text |Cite
|
Sign up to set email alerts
|

Optimized structural properties of wurtzite GaN on SiC(0001) grown by molecular beam epitaxy

Abstract: We have investigated optimal conditions for molecular beam epitaxial growth of high quality GaN on 6H-SiC (0001) substrates. The quality of these films is reflected in both the narrow x-ray peakwidths as well as the excellent surface morphology. In this work, it is shown that increasing growth temperature leads to an improvement in bulk quality and lower xray peakwidth for both symmetric and asymmetric reflections. We also note a marked improvement in surface morphology, from a columnar appearance to a 2-D sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…20 The diffraction pattern contains information about the structure of the crystalline material, which indicates here that the PZT thin film is highly textured in the (001) orientation. 21 There was no trace of a secondary phase due to PbO volatilization, and a single tetragonal phase PZT formed. Figure 1d shows the rocking curve of the PZT thin film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…20 The diffraction pattern contains information about the structure of the crystalline material, which indicates here that the PZT thin film is highly textured in the (001) orientation. 21 There was no trace of a secondary phase due to PbO volatilization, and a single tetragonal phase PZT formed. Figure 1d shows the rocking curve of the PZT thin film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Due to the lack of a native substrate, GaN is mostly grown on foreign substrates, such as AlN, 53 Si, 54 sapphire, 55 and SiC. 56 The mismatch between the two layers results in a high density of threading dislocations in the GaN epilayer, which includes pure edge, pure screw, and mixed dislocations. These dislocations have a significant effect on the device behavior.…”
Section: B Gan Growthmentioning
confidence: 99%
“…Early work [1] asserted that N-rich conditions led to three-dimensional, columnar growth and low electron mobilities [2]. Some research has concluded that growth must be done with the fluxes set to obtain films as close to the stochiometric condition as possible [3], while others maintain that it must be done in the 'intermediate range' (Ga-rich but just short of droplet formation) [4,5]. In any case the window for obtaining Ga rich films without inducing Ga droplet formation is small, and precise determination of the 1:1 condition is important.…”
Section: Introductionmentioning
confidence: 97%